Personalized Learning Website On Topic Of Fraction For Lower Secondary Students - Abu Samah, Norazrena (fakulti pendidikan, 2011)
The need has arises towards the consideration of individual difference includes their learning styles, learning orientations, preferences and needs in learning to let learners engage in and responsible for their own learning, retain information longer, apply the knowledge more effectively, have positive attitudes towards the subject, have more interest in learning materials, score higher and have high intrinsic motivation level. As regard to the importance of individual differences, Martinez (2000) has grounded a new theory that covered individual aspects of cognitive, intention, social and emotion. These aspects are integrated in Learning Orientation Model that categorized students based on how they choose to plan, set, perform and attain goals, intend to commit and expend effort and also, experience learning and achievement. Learning Orientations Questionnaire is the instrument used to categorized learners into four learning orientations profiles. Therefore, a personalized learning website will be developed on the topic of Fraction for Form One students. Intentional Learning Theory is referred in conducting this research. Triangulation Method will be used in this research, which involved questionnaires, interviews, observations and data-logging in data collection method. The website is will be developed to cater the mistakes and misconceptions in the topic of Fraction. Keywords: Learning Website, Fraction & Lower Secondary